1983
DOI: 10.1126/science.6356360
|View full text |Cite
|
Sign up to set email alerts
|

Directed Mutagenesis of Dihydrofolate Reductase

Abstract: Three mutations of the enzyme dihydrofolate reductase were constructed by oligonucleotide-directed mutagenesis of the cloned Escherichia coli gene. The mutations--at residue 27, aspartic acid replaced with asparagine; at residue 39, proline replaced with cysteine; and at residue 95, glycine replaced with alanine--were designed to answer questions about the relations between molecular structure and function that were raised by the x-ray crystal structures. Properties of the mutant proteins show that Asp-27 is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
1
3

Year Published

1984
1984
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(98 citation statements)
references
References 31 publications
1
93
1
3
Order By: Relevance
“…Kraut and co-workers observed that its replacement with Asn led to a fall in apparent overall catalytic competence to 0.1 % of that of the wild type enzyme. (Villafranca et al, 1983), and further studies have confirmed and extended this observation . Crystal structures for the wild type, Asp-27 --Asn, and Asp-27 -+ Ser variants of dihydrofolate reductase were compared at 0.19 nm resolution, and the only apparent structural differences noted, apart from the side chain atoms at the substitution site, were the positions of internally bound water molecules.…”
Section: Al-antitrypsinsupporting
confidence: 54%
“…Kraut and co-workers observed that its replacement with Asn led to a fall in apparent overall catalytic competence to 0.1 % of that of the wild type enzyme. (Villafranca et al, 1983), and further studies have confirmed and extended this observation . Crystal structures for the wild type, Asp-27 --Asn, and Asp-27 -+ Ser variants of dihydrofolate reductase were compared at 0.19 nm resolution, and the only apparent structural differences noted, apart from the side chain atoms at the substitution site, were the positions of internally bound water molecules.…”
Section: Al-antitrypsinsupporting
confidence: 54%
“…However, oligonucleotide or site-directed mutagenesis offers an alternate and much more specific method for testing the role of any amino acid residue by selectively altering DNA codon sequences using in vitro recombinant DNA techniques. While the use of site-directed mutagenesis to study enzyme mechanisms is a field still in its infancy, it is clear from those few examples in the literature (13)(14)(15)(16) that such an approach provides a powerful tool for probing the details of enzymic catalysis. Therefore, we were encouraged to test the predicted role of the oxyanion hole in the subtilisin-catalyzed cleavage of a specific peptide substrate by changing Asn-155 to leucine.…”
Section: <C-nhmentioning
confidence: 99%
“…Oligonucleotide-directed mutagenesis has become a useful means for investigating the structure and function ofproteins (12). We have used the mutagenesis protocol to examine the role of individual amino acids in the reaction mechanism of the poliovirus protease.…”
mentioning
confidence: 99%